1996
DOI: 10.1182/blood.v87.7.2683.bloodjournal8772683
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen modulates the recruitment of myelopoietic cell progenitors in rat through a stromal cell-independent mechanism involving apoptosis

Abstract: Loss of ovarian function leads to a significant increase in the number of bone-resorbing osteoclasts. Estrogen replacement is known to manifest bone protective effects in the treatment of postmenopausal osteoporosis. In the present study, we used ovariectomized rats to examine the effects of estrogen loss at the osteoclast progenitor colony forming unit-granulocyte macrophage (CFU-GM) level. A significant increase in CFU-GM number was observed as early as 7 days following ovariectomy, and correlated directly w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…Estrogens modulate osteoclastogenesis by a double mechanism: an effect on stromal cells/osteoblasts, which produce the indispensable growth factors and cytokines, and a direct effect on osteoclast progenitors. (36,38,43,44) In mouse bone marrow cultures and in the murine monocytic cell line RAW 264.7, the hormone inhibits osteoclast precursor differentiation by a mechanism involving c-Jun repression (40) and by decreasing their responsiveness to RANKL. (41) In this study, we showed that daidzein and estradiol also influence the life span of osteoclast progenitors, because both induce apoptosis of bone marrow cells, as assessed by selective caspase-8 and caspase-3 activation, followed by nuclear fragmentation and formation of apoptotic bodies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estrogens modulate osteoclastogenesis by a double mechanism: an effect on stromal cells/osteoblasts, which produce the indispensable growth factors and cytokines, and a direct effect on osteoclast progenitors. (36,38,43,44) In mouse bone marrow cultures and in the murine monocytic cell line RAW 264.7, the hormone inhibits osteoclast precursor differentiation by a mechanism involving c-Jun repression (40) and by decreasing their responsiveness to RANKL. (41) In this study, we showed that daidzein and estradiol also influence the life span of osteoclast progenitors, because both induce apoptosis of bone marrow cells, as assessed by selective caspase-8 and caspase-3 activation, followed by nuclear fragmentation and formation of apoptotic bodies.…”
Section: Discussionmentioning
confidence: 99%
“…(41) In this study, we showed that daidzein and estradiol also influence the life span of osteoclast progenitors, because both induce apoptosis of bone marrow cells, as assessed by selective caspase-8 and caspase-3 activation, followed by nuclear fragmentation and formation of apoptotic bodies. (45) Other studies have shown that estrogen may modulate the recruitment of rat myelopoietic cell progenitors through a mechanism involving apoptosis (36) and induce apoptosis in a human preosteoclastic cell line. (46) The similar effects of daidzein and 17␤-estradiol suggest that they have a common ER-mediated action.…”
Section: Discussionmentioning
confidence: 99%
“…Estrogens and glucocorticoids regulate the activities of cyclooxygenase (COX) and LOX [25][26][27][28][29][30]. Changes in progenitor cell number and fate also occur following surgical menopause [31][32][33] and altered lipid mediator synthesis may contribute to these changes. We hypothesized that ovariectomy would give raise to an altered profile of LOX-derived lipid mediators in bone marrow such that a relative abundance of proinflammatory as opposed to anti-inflammatory/proresolving lipid mediators would occur.…”
Section: Introductionmentioning
confidence: 99%
“…(15,16) Lack of estrogen results in increased osteoclast number and bone resorbing activity. (17,18) Two different ER genes have been shown. The ER-␣ gene is located on chromosome 6q25-27, comprises eight exons, and spans more than 140 kilobases (kb).…”
Section: Introductionmentioning
confidence: 99%